Structural phase transition in some perovskite materials materials having positive thermoresistive coefficient - Luong, Viet Van; Pham, Cong Thanh; nguyen, Dinh Ngoc; Nguyen, Tuyen Long; Bach, Cong Thanh (VNU Journal of Science: Mathematics - Physics, 2017)
Abstracts